Turbulence models assessment for separated flows in a rectangular asymmetric three-dimensional diffuser. Issue 4 (13th June 2016) - Lu, Lipeng; Zhong, Luyang; Liu, Yangwei
Abstract : Purpose: – The purpose of this paper is to present a full three-dimensional (3D) computational fluid dynamics (CFD) analysis of a rectangular asymmetric 3D diffuser utilizing seven turbulence models frequently used in engineering to assess the predictive capabilities of the turbulence models for separated flows in internal flows. Design/methodology/approach: – The structured computational grids are generated by means of the mesh generation tool IGG software package. The computational grids are imported into the commercial CFD code Fluent. The performance of the different turbulence models adopted has been systematically assessed by comparing the numerical results with the available experimental and direct numerical simulation/large eddy simulations data. Findings: – The comparisons show that the Reynolds stress model (RSM) evidently performs better than the other turbulence models for predicting wall pressure, velocity, and vorticity fields. Moreover, only the RSM can predict the separation bubble region around the top right corner, which is consistent with the experiment. It is found that the RSM can well predict Prandtl's secondary flow of the second kind for considering turbulence anisotropy, whereas the other models cannot. Originality/value: – The paper utilizes seven turbulence models frequently used in engineering in detailed numerical investigations of a real 3D diffuser to expand the scope of application for various turbulence models. The studies are valuable for the proper use of the turbulence models, allowing the designers to understand the numerical results further and contributing to the modification of the turbulence models for 3D flows.